ANALISA SURAT LUQMAN AYAT 12-19 TERKAIT BIMBINGAN KONSELING ISLAMI DI PONDOK PESANTREN MODERN - Naufal Alifuddin Rahman; Imam Fauji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study analyzes the principles of counseling guidance in the Quran, focusing on Surah Luqman verses 12-19, and examines their implementation at the Darussalam Islamic boarding school. A qualitative approach with a descriptive method was employed, utilizing literature review, documentation, and interviews with BK teachers, caregivers, and students. Observations of students' daily behavior and their relationships with caregivers were also conducted. The research revealed that the counseling guidance at Darussalam Islamic boarding school is based on the Quran, particularly Surah Luqman verses 12-19. The "al mauidzah al hasanah" approach, characterized by gentle and kind language, is predominantly used, as it is more easily accepted by students. However, the "bil hikmah" approach is applied to students who are resistant to advice or when the "al mauidzah al hasanah" approach fails to resolve their issues. Interviews with the dormitory head, BK teachers, and students confirmed that the school not only uses the Quran as a teaching tool but also as a means of addressing students' problems. This reflects the integration of Quranic principles into the school's counseling guidance, demonstrating the Quran's role as both a source of knowledge and a practical tool for problem-solving within the school environment.